2020
DOI: 10.1002/jbmr.4154
|View full text |Cite
|
Sign up to set email alerts
|

The Oncosuppressors MEN1 and CDC73 Are Involved in lncRNA Deregulation in Human Parathyroid Tumors

Abstract: A role for long non‐coding RNAs (lncRNAs) in endocrine cancer pathogenesis is emerging. However, knowledge regarding their expression pattern, correlation with known genetic defects, and clinical implications in parathyroid tumors is still unclear. Here, we profiled 90 known lncRNAs in a first series of normal (PaN = 2), adenomatous (PAd = 12), and carcinomatous (PCa = 4) parathyroid glands and we confirmed deregulation of 11 lncRNAs using an independent cohort of patients (PaN = 4; PAd = 26; PCa = 9). Express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Accordingly, regulation of the EMT pathway was one of the top enriched canonical pathways in metastatic compared to non-metastatic PCs. The contribution of lncRNAs to the development of malignant and benign parathyroid tumors has been investigated indifferent studies and some of them might be useful markers in differentiating PCs from PAs (Jiang et al 2019, Morotti et al 2020.…”
Section: :2mentioning
confidence: 99%
“…Accordingly, regulation of the EMT pathway was one of the top enriched canonical pathways in metastatic compared to non-metastatic PCs. The contribution of lncRNAs to the development of malignant and benign parathyroid tumors has been investigated indifferent studies and some of them might be useful markers in differentiating PCs from PAs (Jiang et al 2019, Morotti et al 2020.…”
Section: :2mentioning
confidence: 99%
“…Fresh samples from 20 PAds surgically removed from patients affected with primary hyperparathyroidism were collected and used for gene expression analysis in total tissue RNAs; biochemical, hormonal, and clinical characteristics have been previously published [46]. Fresh samples from further 10 PAds were collected immediately after surgical removal, partly snap-frozen, and partly dissociated for cell cultures.…”
Section: Parathyroid Tissue Samplesmentioning
confidence: 99%
“…The GRch37/hg19 of the Human Genome Reference (March 2009) consortium was used as the reference genome. Data were partially previously published [46].…”
Section: Dna Extraction and Array Comparative Genomic Hybridization (Acgh) Analysismentioning
confidence: 99%
“…The GRch37/hg19 of the Human Genome Reference (March 2009) consortium was used as the reference genome. Data were partially published previously [25].…”
Section: Dna Extraction and Array Comparative Genomic Hybridization (Acgh) Analysismentioning
confidence: 99%
“…Transient silencing of the MEN1 gene in PAds-derived cells (n = 4; Figure 2B) increased SOX2 mRNA levels (Figure 2C), while it did not affect expression of both POU5F1/OCT4 and NANOG (data not shown). Moreover, we previously demonstrated that MEN1 silencing increased the expression of a set of long non-coding RNAs (lncRNAs) in PAds [25]. We focused the attention on the lncRNA HAR1B, whose expression has been found to be upregulated in PAds harboring the Chr.11-LOH and has been upregulated by MEN1-silencing [25].…”
Section: The Core Stem Cell Genes Sox2 Pou5f1/oct4 and Nanog Are Expressed In Parathyroid Tumorsmentioning
confidence: 99%